Verbesserte linksventrikuläre Ruhefunktion und -perfusion nach transluminaler koronarer Angioplastik - Klepzig, H.; Standke, R.; Maul, F.-D.; Kaltenbach, M.; Hör, G. (Nuklearmedizin - NuclearMedicine, 1991)
The purpose of this study was to evaluate left ventricular function and perfusion at rest before and after percutaneous transluminal coronary angioplasty. In consecutive 69 patients in whom coronary stenoses were dilated, the radionuclide left ventricular ejection fraction at rest increased significantly. In 26 of these patients, the ejection fraction increased by at least 4%. In these patients, exercise-induced ischemic ST depression had been more pronounced than in the others. 36 other patients underwent 201TI myocardial scintigraphy before and after angioplasty. Twelve patients in whom pre-PTCA images had revealed regions with irreversible 201TI uptake defects, showed normal 201TI distribution patterns on post-PTCA scintigrams. Post-exercise 201TI uptake (representing myocardial perfusion and metabolic activity) during pre-PTCA exercise stress tests was significantly lower in these cases. It is concluded that PTCA can improve left ventricular function and perfusion at rest. This improvement is most obvious in patients with pronounced exercise-induced myocardial ischemia as diagnosed by typical ST segment depression and reduced thallium uptake.